Pengaruh Independensi, Profesionalisme, Dan Kompetensi Terhadap Kinerja Auditor BPKP - Ririn Dwi Putri Anggraini; Efrizal Syofyan (Universitas Negeri Padang, 2020)
The purpose of this research is to find out the influence of independence, professionalism, and competence on auditors' performance. This research used functional auditors in BPKP Sumatera Barat as population and samples were used Slovin's formula. Descriptive analysis and multiple linear regression were chosen to be methods of this research. The results of this research found out that independence had significant positive influence on auditors' performance, professionalism had insignificant influence on auditors' performance, and competence had significant positive on auditors' performance.